FORENSIC EVALUATION OF DEATHS DUE TO ACUTE ALCOHOL POISONING IN HYDERABAD - Qamar Zaman Phull; Lubna Riaz; Shahla Imran; Sadia Abdul Qayyum; Muzna Hameed Dar; Hanozia Shah (Journal of Ayub Medical College Abbottabad, 2024)
Background: Acute alcohol poisoning, particularly from methanol ingestion, remains a critical public health issue worldwide. In regions where illicit alcohol production thrives, methanol poisoning cases are prevalent, posing severe risks of mortality and long-term morbidity. Aim and objective was to analyze the forensic profiles of deaths due to acute methanol poisoning in Hyderabad, identifying the main causes and contributing factors to fatalities associated with methanol intoxication. Methods: This retrospective descriptive cross-sectional study reviewed 198 autopsy records from a hospital in Hyderabad, focusing on cases identified as methanol intoxication deaths. The study analyzed demographic data, autopsy findings, and toxicological reports. Results: A total of 198 fatalities were recorded, with a significant male predominance (91.9%). The age range of the deceased was 21 to 58 years, with a notable concentration in the 31-40 years age group. High blood methanol concentrations were observed with many cases exceeding the lethal threshold. Autopsy findings highlighted the severe impacts of methanol on the brain, heart, and lungs. Conclusion: The study underscores the grave impact of methanol poisoning in the Hyderabad region, with a high rate of fatalities, particularly among young to middle-aged men. It calls for stricter regulation of alcohol production, increased public awareness, and improved medical recognition and treatment of methanol poisoning.